Comparison of the indications received during experiment and modelling - Фидровская, Наталья Николаевна; Варченко, Иван Сергеевич (Eastern-European Journal of Enterprise Technologies, 2012)
The experimental data of the tensions, appearing on the drum’s covering while the rope had being waved on it, and the tensions achieved from a countable model built in a program SOLID WORKS, were compared in this article